Pengembangan Pribadi Islami dalam Pendidikan Kewirausahaan di SD Islamic Center Samarinda - Kolik, Abdul (UIN Sultan Aji Muhammad Idris Samarinda, 2025)
Education is carried out not only through the delivery of lesson materials and the completion of assignments in the classroom, but also through projects outside the classroom, in order to foster students' abilities and the growth of life experiences within the community. Entrepreneurship education becomes an attractive option for providing valuable experiences for students. This research explores the development of Islamic personal character through entrepreneurship education at SD Islamic Center Samarinda. Using a descriptive qualitative method involving observations, interviews, and documentation, the study finds that entrepreneurship activities, specifically through the